7-Bromo-1,4-bis(prop-2-ynyl)pyrido[2,3-b]pyrazine-2,3(1H,4H)-dione - Meriem Sikine; Youssef Kandri Rodi; Younes Ouzidan; Jerry P. Jasinski; Manpreet Kaur; El Mokhtar Essassi (IUCrData, 2018)
In the title compound, C13H8BrN3O2, the pyrido-pyrazine fused-ring system is essentially planar (r.m.s. deviation = 0.061 Å). The prop-2-ynyl moieties are twisted away from the ring system in opposite directions. In the crystal, a single weak C—H...O interaction generates [010] chains and aromatic π–π stacking interactions between the pyridine rings are observed.